Sokrates populista - Sieradzan, Jacek (Humaniora. Czasopismo Internetowe, 2022)
Platonic Socrates is uncompromising populist who want to show that he is always right. During discussion he uses eristic techniques. He attacks a man, not his views. He uses all methods and arguments in order to avoid essence of discussion when it is awkward for him. He ignores criticism of others, and in discussion he often contradicts oneself. In the end he sacrfices his life in order his ideas and opinions to be survived.